New spectrum of COVID-19 manifestations in children: Kawasaki-like syndrome and hyperinflammatory response - Panupattanapong, Sirada; Brooks, Elizabeth B. (Cleveland Clinic Journal of Medicine, 2020)
In April 2020, data began emerging on Kawasaki-like syndrome and hyperinflammatory response in children with COVID-19. Since then, much has been published on the presentation of COVID-19 in pediatric patients, including its association with Kawasaki disease and the multisystem inflammatory syndrome in children (MIS-C). However, questions still remain regarding the risk factors, pathogenesis, prognosis, and specific therapy for these manifestations of COVID-19.